Analysis of Factors Affecting Lecturers’ Research Quality through the Use of Digital Libraries - Desika Handayani; Ririn Rizki Apdasuli; Desy Eka Citra Dewi (Southeast Asian Journal of Global Trends and Issues in Education, 2025)
Background: The research quality of lecturers is a critical measure of the overall performance of higher education institutions. Digital libraries have become a vital resource in facilitating academic research by offering easy access to a wide array of scholarly materials. However, despite their advantages, many lecturers still face challenges in utilizing digital libraries effectively, impacting the quality of their research. Objective: This study aims to analyze the factors affecting the quality of lecturers’ research through the use of digital libraries, focusing on aspects such as information literacy, access to technology, institutional support, and training. Method: The study employs a qualitative descriptive approach using a literature review method. Relevant articles, books, and academic papers were collected, analyzed, and synthesized to identify key factors influencing research quality. Result: The study finds that factors such as lecturers' information literacy skills, institutional policies, and access to technology are critical in maximizing the use of digital libraries for research. Additionally, the role of librarian support and comprehensive training is significant in improving research quality. Conclusion: Improving digital literacy, providing institutional support, and offering training on the use of digital libraries are crucial for enhancing lecturers' research quality. By addressing these barriers, institutions can help lecturers fully leverage digital libraries to improve their academic output. Contribution; This study contributes to understanding the essential factors that impact the effective use of digital libraries in academic research. The findings can guide higher education institutions in enhancing the support systems and resources available to lecturers, ultimately improving the overall research output of academic staff.